A Bayesian Approach to Latent Class Modeling for Estimating the Prevalence of Schizophrenia Using Administrative Databases - Laliberté, Vincent; Joseph, Lawrence; Gold, Ian (Frontiers in Psychiatry, 2015)
Estimating the incidence and the prevalence of psychotic disorders in the province of Quebec has been the object of some interest in recent years as a contribution to the epidemiological study of the causes of psychotic disorders being carried out primarily in the UK and Scandinavia. A number of studies have used administrative data from the Régie de l’assurance maladie du Québec (RAMQ) that includes nearly all Quebec citizens to obtain geographical and temporal prevalence estimates for the illness. However, there has been no investigation of the validity of RAMQ diagnoses for psychotic disorders, and without a measure of the sensitivity and the specificity of these diagnoses, it is impossible to be confident in the accuracy of the estimates obtained. This paper proposes the use of latent class analysis to ascertain the validity of a diagnosis of schizophrenia using RAMQ data.